Diabetic visceral neuropathy of gastroparesis: Gastric mucosal innervation and clinical significance - Tseng, Ping‐Huei; Chao, Chi‐Chao; Cheng, Ya‐Yin; Chen, Chieh‐Chang; Yang, Ping‐Hao; Yang, Wei‐Kang; Wu, Shao‐Wei; Wu, Yen‐Wen; Cheng, Mei‐Fang; Yang, Wei‐Shiung; Wu, Ming‐Shiang; Hsieh, Sung‐Tsang (European journal of neurology, 2022)
Background and purpose The pathogenesis of diabetic gastroparesis due to visceral neuropathy involves multidimensional mechanisms with limited exploration of gastric mucosal innervation. This study aimed to examine quantitatively this topic and its relationship with gastroparesis symptoms and gastric emptying in diabetes. Methods We prospectively enrolled 22 patients with type 2 diabetes and gastroparesis symptoms and 25 age‐ and gender‐matched healthy controls for comparison. The assessments included: (i) neuropathology with quantification of gastric mucosal innervation density (MID) on endoscopic biopsy; (ii) clinical manifestations based on the Gastroparesis Cardinal Symptom Index (GCSI) questionnaire; and (iii) functional tests of gastric emptying scintigraphy (GES). Results In patients with diabetes, stomach fullness, bloating and feeling excessively full after meals constituted the most common GCSI symptoms. Seven patients with diabetes (32%) had prolonged gastric emptying patterns. In diabetes, gastric MID was significantly lower in all the regions examined compared with the controls: antrum (294.8 ± 237.0 vs. 644.0 ± 222.0 mm/mm3; p < 0.001), body (292.2 ± 239.0 vs. 652.6 ± 260.9 mm/mm3; p < 0.001), and fundus (238.0 ± 109.1 vs. 657.2 ± 332.8 mm/mm3; p < 0.001). Gastric MID was negatively correlated with gastroparesis symptoms and total scores on the GCSI (p < 0.001). Furthermore, gastric MID in the fundus was negatively correlated with fasting glucose and glycated hemoglobin levels. Gastric emptying variables, including half emptying time and gastric retention, were prolonged in patients with diabetes, and gastric retention at 3 h was correlated with fasting glucose level. Conclusion In diabetes, gastric MID was reduced and GES parameters were prolonged. Both were correlated with gastroparesis symptoms and glycemic control. These findings provide pathology and functional biomarkers for diabetic visceral neuropathy of gastroparesis and underlying pathophysiology. In patients with type 2 diabetes, gastric mucosal innervation was reduced and gastric emptying parameters were prolonged. Both were correlated with gastroparesis symptoms and glycemic control. These findings provide pathology and functional biomarkers for diabetic visceral neuropathy of gastroparesis and underlying pathophysiology.